Congenital toxoplasmosis in humans: an update of worldwide rate of congenital infections. Issue 12 (18th October 2021) - Dubey, J. P.; Murata, F. H. A.; Cerqueira-Cézar, C. K.; Kwok, O. C. H.; Villena, I.
Abstract: Abstract: The morbidity due to congenital toxoplasmosis in humans is very high. Most of these infected children are likely to develop symptoms of clinical toxoplasmosis. Sequelae in fetus resulting from Toxoplasma gondii infections in women who become infected with this parasite during pregnancy can be devastating and enormous efforts are directed in some countries to prevent these consequences. Here, an update on congenital toxoplasmosis in humans, especially the rate of congenital infections in humans worldwide, is provided. Although several countries have surveillance programmes, most information on the rate of congenital transmission is from France and Brazil. Because of compulsory national screening programme in France to detect and treat women with recently acquired T. gondii infection with anti-toxoplasma therapy, the rate of congenital transmission and the severity of disease in children are declining. Infections by this parasite are widely prevalent in Brazil. The severity of clinical toxoplasmosis in Brazilian children is very high and may be associated with the genetic characteristics of T. gondii isolates prevailing in animals and humans in Brazil. Virtually little or no information is available on this topic from China, India and other countries in Asia.